Effect of Gaseous Ozone on Transverse and Impact Strengths of Heat Cure Acrylic Resin: An In Vitro Study - Baraa Hasan Kadhim; Wasmaa S Mahmood (Wolters Kluwer Medknow Publications, 2023)
Introduction: This study aimed to find out how exposure to gaseous ozone affected heat-cured acrylic resin's transverse and impact strengths. Methods: Sixty samples of heat-cured acrylic resin were prepared and divided into three subgroups, control, microwave radiation (positive control), and gaseous ozone. Transverse strength and impact strength were evaluated using testing machines. At a level of significance of 5%, data were assessed using one-way analysis of variance (ANOVA) and Tukey's post hoc test. Results: Transverse strength analysis showed a significant difference among groups (P < 0.001). Post hoc test revealed significant differences between all multiple groups (P < 0.001). Impact strength analysis results showed a non-significant difference among groups (P = 0.13). Conclusion: Within the limits of this research, it is possible to conclude that gaseous ozone exposure improves the transverse strength of heat-cure acrylic resin.